Transfer Function Analysis of the Longitudinal Motion of the Common Carotid Artery Wall - Yli-Ollila, Heikki; Tarvainen, Mika P.; Laitinen, Tomi P.; Laitinen, Tiina M. (Frontiers in Physiology, 2016)
The longitudinal motion of the carotid wall is a potential new measure of arterial stiffness. Despite the over decade long research on the subject, the driving force and the specific longitudinal kinetics of the carotid wall has remained unclear. In this study, a transfer function analysis with 20 healthy subjects is presented to derive how the energy from the blood pressure moves the innermost arterial wall longitudinally and how the kinetic energy is then transferred to the outermost arterial layer. The power spectrums display that the main kinetic energy of the longitudinal motion is on band 0-3 Hz with a peak on the 1.1 Hz frequency. There is a large variation among the individuals, how the energy from the blood pressure transfers into the longitudinal motion of the arterial wall since the main direction of the longitudinal motion varies individually and because early arterial stiffening potentially has an effect on the time characteristics of the energy transfer. The energy transfer from the innermost to the outermost wall layer is more straightforward: on average, a 17 % of the longitudinal amplitude is lost and an 18.9 ms delay is visible on the 1.0 Hz frequency.